Calculation of the Longitudinal Electron Scattering Form Factors for the 2s-1d Shell Nuclei - Hamoudi, A. K. (Iraqi Journal of Physics, 2009)
Inelastic longitudinal electron scattering form factors have been calculated for isoscaler transition T = 0 of the (0+ ®2+ ) and (0+ ®4+ ) transitions for the 20Ne ,24Mg and 28Si nuclei. Model space wave function defined by the orbits 1d5 2 ,2s1 2 and 1d3 2 can not give reasonable result for the form factor. The core-polarization effects are evaluated by adopting the shape of the Tassie- Model, together with the calculated ground Charge Density Distribution CDD for the low mass 2s-1d shell nuclei using the occupation number of the states where the sub-shell 2s is included with an occupation number of protons (a ) .